EFFECT OF BIODIVE FERTILIZER ON N, P, AND K NUTRITION STATUS AND GROWTH AND RESULT OF TWO GOGO RICE VARIETIES IN COASTAL AREA - Muhammad Firza Alentamaru T; Yudhi Harini Bertham; Kanang Setyo Hidnarto; Abimanyu Dipo Nusantara (Asosiasi Mikoriza Indonesia, 2022)
This study aims to determine the effectiveness of the application of biological fertilizers on the availability of nutrients N, P, and K in the soil in coastal areas and the yield of upland rice varieties Inpago 10 and Sunggau. This research was conducted from September to December 2019 in Beringin Raya Village, Muara Bangkahulu District, Bengkulu City. The experimental design used was a two-factor Completely Randomized Block Design. The first factor is land rice varieties, namely varieties Inpago and Sunggo, while the second factor is fertilizer input, double inoculant of P solubilizing bacteria + K solubilizing bacteria + N fixing bacteria, double inoculant of AMF + solubilizing bacteria K + N-fixing bacteria , and inorganic fertilizer recommended by AIAT, namely 200 kg Urea/ha, 100 kg SP36/ha, 100 kg KCl/ha. The two factors were combined so that there were 6 treatment combinations which were repeated 4 times so that there were 24 experimental units. Each experimental unit consists of 50 plants so that the total plant population was 50 x 24 = 1,200 plants. The results showed that the use of biological fertilizers in upland rice cultivation in coastal areas was able to increase the availability of N, P, and K nutrients compared to the initial soil and recommended fertilizers. Upland rice varieties suitable for coastal areas are Inpago 10 with fertilizer in the form of a combination of biofertilizers of Phosphate Solubilizing Bacteria + K Solvent Bacteria + N Fixing Bacteria.